Some Intergenerational Arithmetic to Control Public Debt in the EU - Ward Romp; Roel Beetsma; Matthias Busse; Martin Larch (CESifo GmbH, 2025)
Long-term projections are the bedrock of any analysis looking at the sustainability of public finances. This paper computes the changes in economic growth in individual European Union (EU) countries needed for government debt-to-GDP ratios to stay on their baseline trajectories (taken from the European Commission's Debt Sustainability Monitor 2023) under low-fertility, high-fertility, low-migration and high-migration scenarios. These scenarios are provided in the Commission's Ageing Report (2024). We find that deviations of migration from the baseline entail the largest effect on the required rate of economic growth. The effects of the low-fertility scenario kick in only in the very long run and even exceed those of low migration. Our findings inform policymakers on the urgency to apply measures to raise productivity growth. The urgency is heightened by the fact that in some countries demographic projections tend to be optimistic. Whether the necessary measures are taken is eventually a matter of political will more than anything else.
Keywords: H50; H60; J11; J13; 330; demography; migration; fertility; debt; GDP